Certificate of Attendance and Scholarship of Emilio Belaval - Belaval, Emilio S. (My University, 1924)
Certificado de asistencia y beca de Emilio Belaval de Escuela Superior y además indica que se graduó en 1923.
Keywords: Puerto Rico. Department of Education.; Puerto Rico. Departamento de Educación.